2013
DOI: 10.1039/c2an36133g
|View full text |Cite
|
Sign up to set email alerts
|

Positively charged polymer brush-functionalized filter paper for DNA sequence determination following Dot blot hybridization employing a pyrrolidinyl peptide nucleic acid probe

Abstract: As inspired by the Dot blot analysis, a well known technique in molecular biology and genetics for detecting biomolecules, a new paper-based platform for colorimetric detection of specific DNA sequences employing peptide nucleic acid (PNA) as a probe has been developed. In this particular study, a pyrrolidinyl PNA bearing a conformationally rigid d-prolyl-2-aminocyclopentanecarboxylic acid backbone (acpcPNA) was used as a probe. The filter paper was modified to be positively charged with grafted polymer brushe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Because PNA is an electrostatically neutral molecule, it cannot be captured by a positively charged anionexchanger unless hybridized with its complementary DNA target. The captured PNA can then be detected by MALDI-TOF MS (Boontha et al, 2008;Theppaleak et al, 2013aTheppaleak et al, , 2013b or alternatively by enzyme-mediated colorimetric detection (Laopa, Vilaivan, & Hoven, 2013). In this assay, the crude DNA products obtained after PCR can be used directly without prior purification and the analysis can be performed at room temperature under non-stringent conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because PNA is an electrostatically neutral molecule, it cannot be captured by a positively charged anionexchanger unless hybridized with its complementary DNA target. The captured PNA can then be detected by MALDI-TOF MS (Boontha et al, 2008;Theppaleak et al, 2013aTheppaleak et al, , 2013b or alternatively by enzyme-mediated colorimetric detection (Laopa, Vilaivan, & Hoven, 2013). In this assay, the crude DNA products obtained after PCR can be used directly without prior purification and the analysis can be performed at room temperature under non-stringent conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the satisfactory binding properties and specificity of the PNA probe, the success of this approach should also depend upon the physical properties of the anion exchanger, especially the ability to prevent non-specific adsorption of the unhybridized PNA. Q-sepharose, a commercially crosslinked agarose particles bearing quaternary ammonium groups (Boontha et al, 2008), and quaternized poly(dimethylamino)ethyl methacrylate -grafted cellulose paper (Laopa et al, 2013) or magnetic nanoparticles (Theppaleak et al, 2013a(Theppaleak et al, , 2013b were previously used as solid support for the DNA capture. From material science perspective, the issue related to chemical functionality and hydrophobicity/hydrophilicity of the anion exchanger on the DNA capturing is also worth to be explored and has not yet been addressed in previous investigations.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of the detection methods developed for direct detection of unlabelled nucleic acids are based just on hybridisation events using tagged probes. There are sandwich hybridisation approaches with two probes [25], which can also be assisted by ligases to elongate short sequences of miRNAs [26,27], methods based on triple-stem DNA probes [28] and methods which use a single probe to create specific duplexes which can then be identified either by modified surfaces, [29,30] or p19 protein that specifically recognises nucleic acid duplexes [31,32]. These molecular assays based on hybridisation without further molecular recognition are then integrated within different detection systems such as electrochemical sensors [28,30,[32][33][34] and fluorescence-based platforms [26] with variable limit of detections.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraged by the aforementioned features, we have showcased the utility of this PNA as DNA probes in a number of applications. [17][18][19][20][21] In the current study, we aimed to immobilise acpcPNA by covalently attaching the PNA onto cellulose paper, and utilising it as a probe for DNA detection. Aer DNA incubation by capillary method 22 and washing, we demonstrated that cationic organic dyes could be used to visualise the binding between PNA and DNA by electrostatic interaction between the dye and the bound negatively charged DNA (Fig.…”
mentioning
confidence: 99%
“…The fabrication of the sensor commenced with selecting an appropriate chemistry for covalent immobilisation of acpcPNA via an appended lysine residue at the N-or C-termini. The hydroxyl group at C-6 position of the glucose monomer in cellulose is the most common site for functional group interconversion, 23 as it has been used as a "gateway" to attach various chemical scaffolds 8,18,22,[24][25][26] leading to diverse applications ranging from combinatorial synthesis (SPOT and macroarray synthesis) 27 to the immobilisation of biomolecules for sensor construction purposes. 8,22,26 For the ultimate goal of naked-eye detection, we found that not all commonly used chemical reactions are equally suitable, as some attachment methods produced false-positive signal from PNA alone (without the presence of DNAdata not shown).…”
mentioning
confidence: 99%